Fish pluralities: Human-animal relations and sites of engagement in Paulatuuq, Arctic Canada - Todd, Zoe (Études/Inuit/Studies, 2014)
This article explores human-fish relations as an under-theorized “active site of engagement” in northern Canada. It examines two case studies that demonstrate how the Inuvialuit of Paulatuuq employ “fish pluralities” (multiple ways of knowing and defining fish) to negotiate the complex and dynamic pressures faced by humans, animals, and the environment in contemporary Arctic Canada. I argue that it is instructive for all Canadians to understand the central role of humans and animals, together, as active agents in political and colonial processes in northern Canada. By examining human-fish relationships, as they have unfolded in Paulatuuq over the last 50 years, we may develop a more nuanced understanding of the dynamic strategies that northern Indigenous people, including the Paulatuuqmiut (people from Paulatuuq), use to navigate shifting environmental, political, legal, social, cultural, and economic realities in Canada’s North. This article thus places fish and people, together, as central actors in the political landscape of northern Canada. I also hypothesize a relational framework for Indigenous-State reconciliation discourses in Canada today. This framework expands southern political and philosophical horizons beyond the human and toward a broader societal acknowledgement of complex and dynamic relationships between people, fish, and the land in Paulatuuq.